Apakah Koneksi Politik Penting? Peran Penyertaan Modal Negara dan Kinerja BUMN terhadap Penerimaan Negara Bukan Pajak - Rachmadhika, Hendra Arie; Solikin, Akhmad Solikin (Politeknik Keuangan Negara STAN, 2025)
Research objective: This study analyzes the impact of State Capital Participation (PMN) and financial performance of State-Owned Enterprises (SOEs) on Non-Tax State Revenue (PNBP), with political connections as a moderating factor. Method: Using a quantitative approach and multiple regression analysis on 300 observations from 2014–2023 Central Government Financial Reports and public data.Research findings: This research finds that PMN negatively affects PNBP. In contrast, financial performance positively influences PNBP. Interestingly, political connections reduce the negative effect of PMN on PNBP, but they do not alter the relationship between financial performance and PNBP. around the dynamics of PMN, SOE financial performance, and political influence, offering practical value for policymakers, SOE management, and investors in formulating financial strategies and optimizing state revenues.